The dynamics of monthly growth rates in the emergence of complexity, accuracy, and fluency in L2 English writing at secondary school–a learner corpus analysis. (June 2022) - Rokoszewska, Katarzyna Joanna
Abstract: The present paper examines the development of complexity, accuracy, and fluency (CAF) in the emergent field of adolescent L2 writing from the perspective of Complex Dynamic Systems Theory (CDST). The paper reports a panel study whose aim was to investigate the monthly growth rates (MGRs) of ten selected measures of syntactic complexity, lexical complexity, accuracy, and fluency as well as to examine the relationships between the growth rates of these measures in L2 English writing at secondary school. The study was based on The Written English Developmental Corpus of Polish Learners (WEDCPL) which consists of over 1900 texts. The corpus was built on the basis of 21 repeated measurements in the form of essays written by 100 learners over the period of 3 years at secondary school. The results of the study revealed insignificant peaks in the trajectories of the monthly growth rates of all measures, but some significant differences and relationships between the average monthly growth rates (AMGRs), pointing to competition between and support within language subsystems. The findings align with previous research in terms of the nonlinearity and interconnectedness of CAF measures in L2 writing development and provide some practical implications on language instruction and evaluation. Highlights: The monthly growth rates of the CAF measures were non-linear and fluctuant. The CAF measures developed at significantly different average monthly growth rates. Average monthly growth rates formed competitive and supportive relationships. The findings align with previous research on the interaction between subsystems. The findings shed some light on writing development, instruction, and evaluation.